STUDI ETNOFARMASI TUMBUHAN OBAT YANG BERKHASIAT SEBAGAI ANTIHIPERTENSI DI KELURAHAN GALUNG, KECAMATAN LILIRIAJA, KABUPATEN SOPPENG - Sanrang, Balkis Ma’ruf (Makassar Natural Product Journal (MNPJ), 2024)
Medicinal plants are used as an effort to maintain health and as a treatment for a disease. Hypertension is one of the highest causes of death in Indonesia. In knowing medicinal plants which are efficacious as anti-hypertensives, an ethnopharmaceutical study was carried out. Ethnopharmacy is a science that studies the use of drugs and methods of treatment by the community. Soppeng Regency consists of 8 Districts, 21 Villages and 49 Villages, one of which is Galung Village. This research was conducted to find out what plants are used by the people of Galung Village in the treatment of hypertension and how to process them. This research was conducted by surveying people who have knowledge about medicinal plants in the treatment of hypertension with a purposive sampling method. From the results of the study, it was found that 14 medicinal plants were used by the Galung Village community for the treatment of hypertension, which were presented in single or mixed forms.